Erratum 2 to: Search for the HH → bb[bar]bb[bar] process via vector-boson fusion production using proton-proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Antel, Claire; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Jongmanns, Jan; Klassen, Martin; Kolb, Mathis; et al. (Journal of high energy physics, 2021)
One correction is noted for the paper.